Dishonesty under Scrutiny - Jeroen van de Ven; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2014)
We investigate how different forms of scrutiny affect dishonesty, using Gneezy's (2005) deception game. We add a third player whose interests are aligned with those of the sender. We find that lying behavior is not sensitive to revealing the sender's identity to the observer. The option for observers to communicate with the sender, and the option to reveal the sender's lies to the receiver also do not affect lying behavior. Even more striking, senders whose identity is revealed to their observer do not lie less when their interests are misaligned with those of the observer.
Keywords: C91; D83; 330; deception; lies; dishonesty; social image; experiment